The Viking heart : how Scandinavians conquered the world - Herman, Arthur, 1956- (Houghton Mifflin Harcourt, 2021)
"From a New York Times best-selling historian and Pulitzer Prize finalist, a sweeping epic of how the Vikings and their descendants have shaped history and America"--